PENERAPAN METODE THINK-TALK-WRITE UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS X PADA TOPIK LOGARITMA DI SEKOLAH MENENGAH ATAS KUPANG [THE APPLICATION OF THE THINK-TALK-WRITE METHOD TO IMPROVE THE MATHEMATICS COMMUNICATION SKILLS OF GRADE 10 STUDENTS ON LOGARITHM TOPICS AT A SENIOR HIGH SCHOOL IN KUPANG] - Pantow, Edsel Yubil; Sitinjak, Debora Suryani; Dirgantoro, Kurnia Putri Sepdikasari (JOHME: Journal of Holistic Mathematics Education, 2020)
Mathematical communication skills are one of the standard abilities in mathematics learning that students must have. In fact, it was found that the grade 10 students at one of the senior high schools in Kupang were still lacking in communicating both orally and in writing in mathematics learning. They lacked the ability to describe mathematical ideas using written symbols and notations and also lacked the ability to make class presentations using mathematical language. The purpose of this study was to improve students' mathematical communication skills, both written and oral, by applying the Think-Talk-Write method. The method used in this research was classroom action research with the Kemmis and McTaggart model in three cycles. The research instruments used were observation sheets, questionnaires, rubric sheets for oral mathematic communication skills, written mathematical communication skills test sheets, and reflection journals. Based on the results of the analysis, the application of the Think-Talk-Write method can improve mathematical communication ability of grade 10 students at a  senior high school in Kupang. In mathematical communication skills written algebraically or graphically using mathematical terms, the appropriate notation and formula symbols increased by 4.76%. Written communication skill with the arrangement of arguments and generalizations increased by 28.57%. Similarly, the ability to convey mathematical thinking using mathematical language increased by 23.81%. The application of the Think-Talk-Write method can improve students' mathematical communication skills with stages starting from the explanation of the model and learning objectives, the distribution of question worksheets and materials, the think stage, the talk stage, and the write stage.BAHASA INDONESIA ABSTRACT: Kemampuan komunikasi matematis merupakan salah satu standar kemampuan dalam pembelajaran matematika yang harus dimiliki siswa. Pada kenyataannya ditemukan bahwa siswa kelas X pada salah satu sekolah menengah atas Kupang masih kurang dalam berkomunikasi baik secara lisan maupun tulisan dalam pembelajaran matematika. Tujuan dari penelitian ini adalah untuk meningkatkan kemampuan komunikasi matematis siswa baik secara tulisan maupun lisan dengan menerapkan metode Think-Talk-Write. Metode penelitian yang digunakan adalah penelitian tindakan kelas dengan model Kemmis dan Mc. Taggart dalam tiga siklus. Instrumen penelitian yang digunakan dalam penelitian ini yaitu lembar observasi, lembar angket, lembar rubrik kemampuan komunikasi matematis lisan, lembar tes kemampuan komunikasi matematis tertulis, dan jurnal refleksi. Berdasarkan hasil analisis, kemampuan komunikasi matematis tertulis secara aljabar atau grafik yang menggunakan istilah matematika, simbol notasi dan formula baku yang sesuai mengalami peningkatan sebesar 4,76%. Pada kemampuan komunikasi tertulis dengan susunan argumen dan generalisasi mengalami peningkatan sebesar 28,57%. Begitu juga pada kemampuan menyampaikan pemikiran matematis menggunakan bahasa matematis mengalami peningkatan sebesar 23,81%. Sehingga dapat disimpulkan bahwa penerapan metode Think-Talk-Write dapat meningkatkan kemampuan komunikasi matematis siswa dengan tahapan mulai dari penjelasan model dan tujuan pembelajaran, pembagian lembar kerja soal dan materi, tahap Think, tahap Talk, dan tahap Write.